PENGENDALIAN PERSEDIAAN BAHAN BAKU DAUN TEH BROKEN PECCO 1 MENGGUNAKAN METODE EOQ (ECONOMIC ORDER QUANTITY) PADA PERUSAHAAN AGROINDUSTRI PT XYZ - Ramadhan, Muhammad Fikri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research was performed because the raw material inventory control has not used any specific methods in agroindustry company PT XYZ which resulted in the stacking of raw material inventory in the storage warehouse and the number of orders each time ordering raw materials that have not been set so that the cost of ordering and handling cost have not been controlled. The cost of raw material inventory can be minimized by the application of EOQ (Economic Order Quantity) method. This method can show the quantity of economic order, optimal purchase frequency, time to re-order/ROP (Re-Order Point), and the amount of safety raw material/safety stock. This research aims to know raw material inventory control processes with actual conditions of the company and the influence of EOQ method implementation on the total of raw materials inventory costs. Data collection was carried out by observation and interviews, while the analysis used the formulation of EOQ method by taking into account of TIC (Total Inventory Cost), ROP, reorder frequency, and safety stock. The results of calculation and data analysis using EOQ method shows the total cost of inventory is lower when compared with the actual method of the company. EOQ method can also help the company to reduce the influence of fluctuation in demand of production process that is not stabilized. Keywords: Inventory Control, Agroindustry, Economic Order Quantity, Total Inventory Cost, Re-Order Point, Safety Stock.